Responding To Afghanistan's Opium Economy Challenge : Lessons And Policy Implications From A Development Perspective - Byrd, William Anderson 1989- (The World Bank, 2008)
Opium, Afghanistan's leading economic activity, lies at the heart of the challenges the country faces in state building, governance, security, and development. With their narrow law enforcement focus and limited recognition of development, security, and political implications, current global counter-narcotics polices impose a heavy burden on Afghanistan. This paper first provides a summary overview of Afghanistan's opium economy and the factors determining rural households' decisions on cultivating opium poppy. It then discusses the dynamic evolution of the Afghan drug industry in recent years, in particular its consolidation around fewer, powerful, politically-connected actors and the associated compromising of parts of some government agencies by drug industry interests. The paper reviews the experience with different counter-narcotics interventions, analyzes some proposals not yet tried in Afghanistan, and draws lessons and policy implications. Unfortunately there are no "silver bullets"-easy, quick, or one-dimensional solutions, and a longer-term horizon along with sustained commitment and resources will be required in order to phase out the opium economy over time. The paper concludes by putting forward some broad principles and approaches of a "smart strategy" against drugs in Afghanistan